A Single-Center, Randomized, Controlled Comparison of the Transradial vs Transfemoral Approach for Cerebral Angiography: A Learning Curve Analysis. (October 2019) - Liu, Yandong; Wen, Xingzhu; Bai, Jun; Ji, Xiangguo; Zhi, Kangkang; Qu, Lefeng
Purpose: To compare the characteristics and learning curve of the transfemoral approach (TFA) vs the transradial approach (TRA) for cerebral angiography.Materials and Methods: Between February 2016 and April 2017, 101 patients undergoing cerebral angiography were enrolled. Fifty-one patients (mean age 67 years; 40 men) were randomized to TFA and 50 (mean age 68 years; 41 men) to TRA using a computer-generated random table. The patients' demographic and angiographic data were recorded and analyzed. The learning curve of a novice interventionist was analyzed for procedure time, puncture time, fluoroscopy time, and contrast volume as markers of technical proficiency with TFA compared with TRA. Median values are given with the interquartile range (IQR).Results: Procedure time [35 (IQR 30, 47.5) vs 31.0 (IQR 25.0, 48.9) minutes, p=0.16), fluoroscopy time [10.3 (IQR 7.6, 13.9) vs 9.4 (IQR 6.1, 17.6) minutes, p=0.70], contrast volume [105 (IQR 92, 120) vs 95.5 (IQR 90, 111.3) mL, p=0.13), radiation exposure [390.2 (IQR 268.2, 617.9) vs 455.8 (IQR 286.8, 602.3) mGy, p=0.74], and the number of catheter exchanges [1 (IQR 1, 3) vs 1 (IQR 1, 1), p=0.06] were not significantly different between the TFA and TRA groups, respectively, but puncture time was shorter with TFA than with TRA [0.6 (IQR 0.5, 1.1) vs 1 (IQR 0.6, 1.9) minutes, p=0.01]. The learning curve was steeper with TRA than with TFA in the beginning stages of training, but with increasing experience, the procedure and fluoroscopy times were better for TRA than for TFA. Training progress was made earlier in TRA.Conclusion: TRA is a reasonable alternative to TFA for cerebral angiography. TRA has a shorter learning curve for novice interventionists.